Associate Professor Dr. Norhayati designs simulator for COVID-19 pandemic stochastic modelling - Nur Hartini, Mohd Hatta (2022)
PEKAN, 8 June 2022 – The COVID-19 pandemic recorded a sharp increase in the use of intensive care unit (ICU) beds and equipment in hospitals around the world and particulalry in the Ministry of Health Malaysia (MOH).